ENERAPAN METODE SIMPLEKS UNTUK OPTIMASI PRODUKSI IKAN AIR TAWAR DAN IKAN AIR PAYAU DI KABUPATEN CILACAP SERTA ANALISIS KELAYAKAN PRODUKSI SECARA SENSITIVITAS - Listyaningrum, Rostika; Afiati, Ika Nur (Infotekmesin, 2018)
Cilacap Regency is one of region whose good potential in process of waterpark cultivation. The resource potential of fresh water cultivation and brackish water and is distribution is almost in CilacapRegency, and it still has potential to develop. This research discussed the application of simplex method on the productivity of fresh water cultivation and brackish water in Cilacap Regency. The optimal solution from simplex method was tested its change of reliability with sensitivity analysis. The maximum productivity of fresh water and brackish water in 2014 till 2016 was 28.784,4494 tons.